NAADP Receptors - Galione, A (2011)
Of the established Ca2+ mobilizing messengers, NAADP is arguably the most tantalizing. It is the most potent, often efficacious at low nanomolar concentrations. Recent studies have identified a new class of calcium release channel, the two-pore channels (TPCs), as the likely targets for NAADP. These channels are endolysosomal in localization where they mediate local Ca2+ release, and have highlighted a new role of acidic organelles as targets for messenger-evoked Ca2+ mobilization. Three distinct roles of TPCs have been identified. The first is to effect local Ca2+ release that may play a role in endolysosomal function including vesicular fusion and trafficking. The second is to trigger global calcium release by recruiting Ca2+-induced Ca2+ release (CICR) channels at lysosomal-ER junctions. The third is to regulate plasma membrane excitability by the targeting of Ca2+ release from appropriately positioned subplasma membrane stores to regulate plasma membrane Ca2+activated channels. In this review, I discuss the role of NAADP-mediated Ca2+ release from endolysosomal stores as a widespread trigger for intracellular calcium signaling mechanisms, and how studies of TPCs are beginning to enhance our understanding of the central role of lysosomes in Ca2+ signaling. © 2011 Cold Spring Harbor Laboratory Press.